Commitment-based human resource practices, job satisfaction and proactive knowledge-seeking behavior: The moderating role of organizational identification - Aleksandra Rudawska (Central European Management Journal)
Purpose – Based on social exchange theory and social identification theory, I investigated how employee organizational identification affects the effectiveness of commitment-based human resource (HR) practices. I focused on employee attitudes (job satisfaction) and behaviors (proactive knowledge seeking) as HR practices’ outcomes. Design/methodology/approach – Using a structural equation modeling analytical approach, I tested the hypotheses with data from a web-based cross-sectional survey of 208 specialists and engineers of manufacturing subsidiaries in Poland. Findings – Results showed that the positive relationship between commitment-based-HR practices and job satisfaction is weakened for employees strongly identified with the organization. Simultaneously, the connection between seeking knowledge and job satisfaction is stronger and more important for people who identify moderately to strongly. Research limitations/implications – The study limitations regard mainly its cross-sectional design and single cultural and industrial context. Practical implications – From the managerial perspective, the study suggests that to enhance proactive employee behavior, companies need to increase employee organizational identification and ensure that employees have a positive perception of the implemented HR practices. Originality/value – The study contributes to the ongoing discussion on whether individual contingencies affect the effectiveness of commitment-based HR practices in the form of individual attitudinal and behavioral outcomes. The findings revealed that the contingent effect of organizational identification depends on the type of individual outcomes, suggesting that the strength of organizational identification affects how employees decide to reciprocate the organization’s attention and investment.